Driver's visual attention to different categories of roadside advertising signs. (July 2019) - Costa, Marco; Bonetti, Leonardo; Vignali, Valeria; Bichicchi, Arianna; Lantieri, Claudio; Simone, Andrea
Abstract: Roadside advertising signs are a salient potential source of driver's distraction. Previous research has mainly investigated driver's visual attention to billboards, which represents only one category of advertising signs. In this study, driver's visual attention was assessed in a naturalistic driving setting for six categories of roadside advertising signs: vendor signs, billboards, movable display boards, single and multiple commercial directional signs, and gas price LED displays. Fixation rate, fixation duration, fixation distance and driving speed were assessed in a sample of 15 drivers along a 30-km route including a total of 154 advertising signs belonging to the six categories described above. The role of clearance from the road, elevation, height, width, surface, number and size of characters, total number of characters, side of the road (driving side, opposite side), context (rural, urban), were also considered. Overall 24% of the roadside advertising signs were fixated. Fixation rate was significantly influenced by sign category, clearance from the road and number of characters. Median value for fixation duration was 297 ms. Fixation duration was significantly influenced by speed, elevation from road level, number of medium size characters, and was higher in the rural context. Median value for fixation distance was 58.10 m, and was significantly influenced by advertising sign category, character count and speed. Highlights: Drivers looked at 24% of roadside advertising signs. Median value for fixation duration to roadside advertising signs was 297 ms. Median value for fixation distance to roadside advertising signs was 58.10 m. Advertising sign category, side, size, and amount of text significantly influenced fixation rate and fixation duration.